Solutions for developing Chinese language teaching at universities in Vietnam from the perspective of Chinese language propagation - Linh, Chi Tran (Edelweiss Applied Science and Technology, 2025)
This comprehensive study investigates the development and current landscape of Chinese language education in Vietnam, contextualized within the broader framework of international Chinese language promotion initiatives. Employing a qualitative research methodology, the study integrates document analysis and case studies from selected Vietnamese universities to evaluate the theoretical underpinnings, historical progression, and contemporary conditions of Chinese language instruction. The findings indicate that, at a macro level, strategic enhancements are imperative, including the formulation of more effective government policies, targeted training programs for educators, stringent administrative oversight, and the implementation of incentive structures to motivate lecturers. Additionally, fostering educational exchanges with China, expanding collaborative initiatives, and establishing Confucius Institutes are recommended to bolster the program. On a micro level, the study emphasizes the importance of localizing Chinese language instruction through recruiting and professionally developing domestic educators, developing culturally and contextually relevant teaching materials, and adopting innovative pedagogical approaches aligned with international standards. The research concludes that addressing systemic and operational deficiencies is vital for elevating the quality of Chinese language education. These insights offer both theoretical and practical guidance for policymakers and serve as a valuable reference for educators aiming to align their practices with global best standards, thereby contributing to the sustainable development of Chinese language education in Vietnam.